Some Types of Archaisms in Polish Dialects in Lithuania - Viktorija Ušinskienė (Slavistica Vilnensis, 2019)
The subject of the article is related to the author’s work on the international project “Polish Dialects in Lithuania” (“Gwary polskie na Litwie”, 2016–2018). The purpose of this paper was to identify and study lexical archaisms in the dialect material selected by the project group. In the article the concept of ‘archaism’ is interpreted widely: both archaic and obsolete words are considered. In total, it was identified about 200 lexical units classified as obsolete or archaic: proper lexical archaisms constitute approximately 50% of the material (arenda, bachur, czernica etc.), semantic archaisms constitute about 35% (baczyć, cacka, czeladź etc.), and about 15% of the material are lexical word-building archaisms (kradkiem, lenować się, nadgrobek etc.). By comparing the studied material with the data of the historical sources, it was possible to realize that a number of lexemes qualified in some scientific papers as regionalisms borrowed from the Eastern Slavic languages should be recognized as archaisms, once known to the common Polish language. Тhe results allow us to confirm the undoubtedly significant role of the Belarusian and Russian languages in supporting the functioning of lexical archaisms in Polish dialects in Lithuania. About half of the identified lexical archaisms are also known to a number of dialects in Poland.